2006
DOI: 10.1530/rep.1.00885
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of expression of growth differentiation factor-9 receptor type I and II genes in the bovine ovarian follicle

Abstract: Growth differentiation factor-9 (GDF-9) and bone morphogenetic proteins (BMPs) are crucial factors in follicular growth and development. GDF-9 and BMPs initiate signaling by assembling type I (ALK-3, ALK-5 and ALK-6) and type II (BMPRII) receptors. However, the mechanism regulating the expression of these receptors in the process of bovine follicle development is still unknown. The aim of the present study was to clarify the involvement of receptor systems for GDF-9 and BMPs in follicular selection by examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 45 publications
(44 reference statements)
2
36
0
1
Order By: Relevance
“…However, combined treatment with FSH and oestradiol increased the expression of all investigated genes, i.e., BMPRII, BMPRIB and ALK-5. This observation supported data from previous studies suggesting the existence of paracrine activation pathways between oocytes and granulosa cells, and the regulation of BMP15 receptors by FSH and E 2 secretion (Jayawardana et al 2006;Chen et al 2009a). Furthermore, it is evident that hormones of the pituitary and ovary have a significant role in the regulation of granulosa cell differentiation.…”
Section: Tgf Gene Expression In Relation To Angiogenesis and Folliculsupporting
confidence: 90%
“…However, combined treatment with FSH and oestradiol increased the expression of all investigated genes, i.e., BMPRII, BMPRIB and ALK-5. This observation supported data from previous studies suggesting the existence of paracrine activation pathways between oocytes and granulosa cells, and the regulation of BMP15 receptors by FSH and E 2 secretion (Jayawardana et al 2006;Chen et al 2009a). Furthermore, it is evident that hormones of the pituitary and ovary have a significant role in the regulation of granulosa cell differentiation.…”
Section: Tgf Gene Expression In Relation To Angiogenesis and Folliculsupporting
confidence: 90%
“…However, a positive correlation was observed between mRNA expression of BMPR2 in PCOS cumulus cells and levels of testosterone and androstenedione in FF from pre-ovulatory follicles. In fact, several studies have shown that BMP receptors are hormonally regulated [22][23][24]. PCOS-related hyperandrogenism can exerts complex effects on the ovarian follicle.…”
Section: Discussionmentioning
confidence: 99%
“…Data from microarray studies indicate that androgen might play a role in up-regulate gene expression in PCOS oocytes [5] and androgen treatment in female rhesus monkeys increases mRNA expression of FSH and IGF-1 receptors in granulosa cells and follicle primordial oocytes [39]. In bovine granulosa cells, estrogen used alone and in combination with FSH has been shown to up-regulate BMPR2 mRNA expression [22,24]. Supporting this finding, a study using a human granulosa-like tumor cell line showed that FSH up-regulated BMPR2 in GCs [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible way to achieve this effect could be down-regulation of TGFB1 action. Indeed, some studies provide evidence that FSH treatment decreases TGFB1 and TGFBR1 (activin receptor-like kinase 5) mRNA expressions in cultured bovine granulosa cells (Nilsson et al 2003, Jayawardana et al 2006. Further studies, including experiments involving manipulation of TGFB1 activity in vivo and in vitro, will be required explore these possibilities.…”
Section: Tgfb1 Regulation Of Steroidogenesis and Apoptosismentioning
confidence: 99%